Black phosphorus polyether-ether-ketone modified antistatic composite material and application thereof

By combining maleic anhydride grafted modified polyether ether ketone with modified black phosphorus nanosheets and other components, a black phosphorus polyether ether ketone modified antistatic composite material was prepared, which solved the problem of sacrificing mechanical properties of black phosphorus modified materials in the prior art, and achieved widespread application of materials in high-end applications.

CN119552470APending Publication Date: 2025-03-04GUANGDONG ZHONGCHENG SPECIAL MATERIALS CO LTD

Patent Information

Application Number
CN202411839190.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art failed to prepare composite materials with black phosphorus and polyether ether ketone (PEEK), resulting in the black phosphorus modified material sacrificing the mechanical properties of the material while maintaining its antistatic properties, limiting its promotion in high-end applications.

Method used

A black phosphorus polyether ether ketone modified antistatic composite material was prepared by grafting modified polyether ether ketone (PEEK) with modified black phosphorus nanosheets, functionalized graphene quantum dots, interface modifiers, antioxidants and processing aids.

Benefits of technology

It realizes that the composite materials have good antistatic properties while maintaining excellent mechanical properties, and are suitable for high-end applications such as automotive parts, engine accessories, power battery shells, charging guns and charging piles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187549170000111
    Figure BDA0005187549170000111
  • Figure BDA0005187549170000121
    Figure BDA0005187549170000121
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials, and particularly relates to a black phosphorus polyether-ether-ketone modified antistatic composite material and application. The composite material comprises the following raw materials in parts by mass: 100 parts of modified polyether-ether-ketone, 3-8 parts of modified black phosphorus nanosheets, 0.5-3 parts of functionalized graphene quantum dots, 0.5-2 parts of an interface modifier, 0.5-1 part of an antioxidant and 1-3 parts of a processing aid. According to the material, the problem of high surface resistivity of a traditional PEEK material is solved, the material is endowed with excellent antistatic performance, and meanwhile, the original mechanical strength is kept. Through the improvements, the composite material shows important actual value and market prospect in the high-end application fields of automobile parts, engine accessories, power battery shells, charging guns, charging piles and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a black phosphorus polyetheretherketone modified antistatic composite material and application thereof. Background Art

[0002] In the field of modern industrial production and electronic products, the generation and accumulation of static electricity has become a problem that cannot be ignored. Static electricity may not only cause damage to electronic components, but also cause safety accidents such as fire and explosion. Especially in industries that are sensitive to static electricity, such as semiconductors, electronic equipment, and precision instruments, the demand for antistatic materials is growing. Polyetheretherketone (PEEK), as a high-performance engineering plastic, is widely used in aerospace, automobile manufacturing, electronics and electrical fields due to its excellent mechanical properties, chemical resistance, heat resistance and wear resistance. However, PEEK itself has a high surface resistivity and does not have antistatic properties, which limits its use in certain specific application scenarios.

[0003] As a new type of two-dimensional material, black phosphorus has attracted widespread attention due to its unique electronic structure and excellent electrical conductivity. Black phosphorus has high electron mobility and adjustable band gap, which makes it show great application potential in electronic devices, energy storage and catalysis. In particular, the conductive properties of black phosphorus give it a unique advantage in the preparation of antistatic materials. By combining black phosphorus with polymer materials, composite materials with both antistatic properties and excellent mechanical properties can be prepared.

[0004] At present, there have been some research reports on the composite of black phosphorus with other polymer materials to prepare antistatic materials. For example, patent 202210573146.X discloses a PET-based conductive masterbatch, film, fiber and its preparation method and application. The material is prepared by co-granulation of a composite conductive medium containing black phosphorus, a dispersant, PET polyester, and PET-PEG copolyester. The material has a low surface resistance. Patent CN202110040156.2 discloses a flame retardant and antistatic glass fiber reinforced nylon 6 composite material and a preparation method thereof. The composite material is prepared from branched nylon 6 flame retardant and antistatic masterbatch, nylon 6 chips, glass fiber and processing aids. Among them, the branched nylon 6 flame retardant and antistatic masterbatch is composed of branched nylon 6, black phosphorus nanosheets and Mxene two-dimensional materials. The prepared material has flame retardant and antistatic effects.

[0005] The existing technology has not yet studied the preparation of composite materials with black phosphorus and PEEK. While maintaining the antistatic properties, the existing black phosphorus modified materials often sacrifice other properties of the material, such as mechanical strength, which limits their promotion in high-end application fields.

[0006] In summary, the development of a black phosphorus polyetheretherketone modified composite material with both good antistatic properties and excellent mechanical properties has important practical application value and market prospects. Summary of the invention

[0007] The object of the present invention is to provide a black phosphorus polyetheretherketone modified antistatic composite material and its application. The composite material not only maintains the excellent mechanical properties of PEEK by improving the formula design, but also gives the material good antistatic properties. This composite material can be particularly applied to the fields of automotive parts, engine accessories, power battery shells, charging guns and charging piles, and has important practical application value and market prospects.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] A black phosphorus polyetheretherketone modified antistatic composite material comprises the following raw materials in parts by mass: 100 parts of modified polyetheretherketone, 3-8 parts of modified black phosphorus nanosheets, 0.5-3 parts of functionalized graphene quantum dots, 0.5-2 parts of an interface modifier, 0.5-1 parts of an antioxidant and 1-3 parts of a processing aid.

[0010] Furthermore, the modified polyetheretherketone is polyetheretherketone modified by grafting with maleic anhydride.

[0011] Furthermore, the preparation method of the modified polyetheretherketone comprises the following steps:

[0012] (1) mixing polyetheretherketone and toluene, heating to 70-90° C., stirring to completely dissolve the polyetheretherketone, and obtaining a mixture;

[0013] (2) adding dibenzoyl peroxide and maleic anhydride to the mixture of step (1), heating to 170-190° C., and stirring for reaction for 1-3 hours;

[0014] (3) After the reaction is completed, the reactant is cooled to room temperature, ethyl acetate is added, filtered, and the precipitate is washed with deionized water and dried to obtain the modified polyetheretherketone.

[0015] Furthermore, in step (1), the mass volume ratio of polyetheretherketone to toluene is 1 g: (2-4) mL.

[0016] Furthermore, the molar ratio of the polyetheretherketone, maleic anhydride and dibenzoyl peroxide is 1:(0.03-0.06):(0.003-0.006).

[0017] The present invention uses maleic anhydride to modify polyetheretherketone (PEEK). Due to the introduction of polar functional groups, the modified PEEK can better interact with inorganic fillers such as black phosphorus nanosheets and graphene quantum dots, thereby improving the overall performance of the composite material. The grafted maleic anhydride can also serve as a bridge to connect conductive fillers and build an effective conductive network, which can effectively reduce the volume resistivity and achieve an ideal antistatic level. In addition, maleic anhydride grafting modification can also improve the fluidity of PEEK by reducing the melt index, making it easier to process and shape.

[0018] Furthermore, the preparation method of the modified black phosphorus nanosheets comprises the following steps:

[0019] (a) using a diamond tool to cut a black phosphorus single crystal into a thin slice with a thickness of 40-60 μm, immersing the black phosphorus slice in an aqueous solution of ammonium persulfate with a concentration of (3-6) wt%, and standing at room temperature for 1-3 hours, then taking out the black phosphorus slice, washing it with deionized water, and drying it;

[0020] (b) adding the dried black phosphorus flakes to N-methylpyrrolidone solvent to make the mass fraction of black phosphorus reach 1-2 mg / mL, and placing the mixture in an ice bath for ultrasonic treatment for 20-40 minutes to obtain a black phosphorus nanosheet suspension;

[0021] (c) preparing an isopropanol solution containing 3-aminopropyltriethoxysilane, adding the black phosphorus nanosheet suspension obtained in step (b) to the isopropanol solution of 3-aminopropyltriethoxysilane, heating to 30-50° C., stirring for reaction for 5-8 hours, centrifuging the reactant, washing the solid alternately with deionized water and ethanol, and drying to obtain the modified black phosphorus nanosheet.

[0022] Furthermore, the pH value of the ammonium persulfate aqueous solution is adjusted to 2-4.

[0023] Furthermore, the mass concentration of the isopropanol solution of 3-aminopropyltriethoxysilane is 1.5-2.5%.

[0024] Black phosphorus has a high electron mobility and an adjustable band gap, and exhibits good electrical conductivity. Composite black phosphorus with polymer materials can give the material excellent antistatic properties. However, when black phosphorus is directly added to the formula of the present invention, it has poor compatibility with other components, resulting in a decrease in the mechanical properties of the material. The modified black phosphorus nanosheets prepared by the present invention can better interact with the polymer matrix and other fillers, thereby achieving a more uniform dispersion, avoiding local stress concentration, preventing the composite material from delamination or peeling under stress conditions, and improving the mechanical properties of the material. After the present invention makes black phosphorus into nanosheets and performs appropriate functionalization, its conductive properties can be further optimized. The functionalized functional groups can adjust the band gap width of the black phosphorus nanosheets, while promoting the formation of electron transmission paths, which can dissipate static charges faster and reduce the risk of static electricity accumulation.

[0025] Furthermore, the method for preparing functionalized graphene quantum dots comprises the following steps:

[0026] (i) mixing graphite powder and sulfuric acid in an ice bath, adding potassium permanganate while stirring, maintaining the temperature at 0-5° C., and continuously stirring for 1-3 hours to form graphite oxide. After the reaction is completed, hydrogen peroxide is added to terminate the reaction, and the graphite oxide is washed with deionized water until the pH value of the solution is neutral;

[0027] (ii) dispersing the graphite oxide obtained in step (i) in water and subjecting it to ultrasonic treatment for 2-5 hours to obtain a graphene oxide dispersion;

[0028] (iii) mixing the graphene oxide dispersion with hydroiodic acid, heating the mixture to 70-90° C. by microwave, maintaining the mixture for 20-40 minutes, cooling the mixture to room temperature, adding L-ascorbic acid, and stirring the mixture for 1-3 hours to obtain a graphene quantum dot dispersion;

[0029] (iv) adding 4-aminobenzaldehyde to the graphene quantum dot dispersion, stirring for 20-30 hours, centrifuging and washing the solid matter to obtain the functionalized graphene quantum dots.

[0030] Furthermore, the sulfuric acid in step (i) is a sulfuric acid aqueous solution with a mass concentration of 98%, the mass volume ratio of graphite powder to sulfuric acid is 1 g: (20-30) mL, and the mass ratio of graphite powder to potassium permanganate is 1: 0.3-0.6.

[0031] Furthermore, in step (iii), the mass of the hydroiodic acid is 8-15 times that of the graphite powder, the mass of the L-ascorbic acid is 0.3-0.8 times that of the graphite powder, and the mass of the 4-aminobenzaldehyde in step (iv) is 0.05-0.2 times that of the graphite powder.

[0032] Graphene quantum dots have a unique electronic structure and quantum confinement effect, and exhibit excellent electrical properties. Through functional treatment, the band gap width of graphene quantum dots can be adjusted, affecting the carrier transmission path, promoting electron transmission, and improving the antistatic effect.

[0033] Furthermore, the interface modifier is a mixture of γ-aminopropyltriethoxysilane, titanium isooctanoate and perfluoropolyether siloxane, with a mass ratio of (4-5): (2-3): 1.

[0034] The present invention adopts three different types of coupling agents as interface modifiers, which solves the limitations of a single component, gives full play to the advantages of each component, and achieves multi-faceted performance improvements. The cross-linking points provided by γ-aminopropyltriethoxysilane and titanium isooctanoate effectively disperse stress, while perfluoropolyether siloxane reduces interface friction and improves the flexibility and impact resistance of the material. The amino group of γ-aminopropyltriethoxysilane can form hydrogen bonds or covalent bonds with other conductive fillers to construct a continuous conductive path. At the same time, perfluoropolyether siloxane helps to reduce volume resistivity and improve antistatic effect.

[0035] Furthermore, the antioxidant is a mixture of antioxidant 168 and antioxidant 1076, with a mass ratio of 1:0.3-0.6.

[0036] Furthermore, the processing aid is zinc stearate or calcium stearate.

[0037] The present invention also provides a method for preparing the above-mentioned black phosphorus polyetheretherketone modified antistatic composite material, comprising the following steps:

[0038] (1) mixing and stirring the modified black phosphorus nanosheets, functionalized graphene quantum dots, an interface modifier, an antioxidant and a processing aid to obtain a premix;

[0039] (2) adding the premix into a twin-screw extruder, adding modified polyetheretherketone at the same time, extruding and granulating to obtain the black phosphorus polyetheretherketone modified antistatic composite material.

[0040] The present invention also provides the use of the above-mentioned black phosphorus polyetheretherketone modified antistatic composite material in automobile body parts, engine accessories, power battery shells, charging guns and charging piles.

[0041] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0042] The present invention provides a black phosphorus polyetheretherketone modified antistatic composite material and its application, which solves the problem of high surface resistivity of traditional PEEK materials, gives the material excellent antistatic properties, and maintains the original mechanical strength. In the formula, PEEK is modified by maleic anhydride grafting, which not only enhances the compatibility with inorganic fillers, but also constructs an effective conductive network, thereby greatly reducing the volume resistivity and achieving an ideal antistatic effect. After surface modification, the modified black phosphorus nanosheets show better dispersibility and stability in the composite material, avoid agglomeration, and further improve the overall performance of the material. The introduction of functionalized graphene quantum dots optimizes the electron transmission path and enhances the conductivity efficiency. The combined use of interface modifiers effectively disperses stress and reduces interface friction, thereby improving the flexibility and impact resistance of the material. These improvements enable the composite material to show important practical value and market prospects in high-end application fields such as automotive parts, engine accessories, power battery shells, charging guns and charging piles. The present invention not only broadens the scope of application of PEEK, but also provides strong support for the safety and development of related industries. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Unless otherwise specified, the raw materials used in the examples are all common commercially available products. The following is an exemplary description:

[0045] Polyetheretherketone was purchased from Shanghai Yuejin Plastic Co., Ltd., PEEK-1000;

[0046] Black phosphorus single crystals were purchased from the Institute of Semiconductors, Chinese Academy of Sciences;

[0047] Black phosphorus powder was purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., BP-100;

[0048] 3-Aminopropyltriethoxysilane was purchased from Guangzhou Huifu Chemical Industry Co., Ltd.;

[0049] Titanium isooctanoate was purchased from Shandong Luxi Chemical Group;

[0050] Perfluoropolyether siloxane was purchased from Beijing Keruibo Technology Development Co., Ltd.;

[0051] Graphite powder was purchased from Qingdao Haida Graphite Products Co., Ltd., HD-Graphite 99.9%;

[0052] Carbon nanotubes were purchased from Changzhou Sixth Element Materials Technology Co., Ltd., MWCNT-500;

[0053] Zinc stearate was purchased from Zhejiang Xin'an Chemical Industry Group Co., Ltd.

[0054] Example 1

[0055] This embodiment provides a method for preparing modified polyetheretherketone, comprising the following steps:

[0056] (1) PEEK and toluene were added to a 250 mL three-necked flask at a mass volume ratio of 1 g:3 mL. A mechanical stirrer, thermometer, and condenser were installed. The three-necked flask was placed in an oil bath and heated until PEEK was completely dissolved. The temperature was controlled at 80 °C.

[0057] (2) under stirring, adding dibenzoyl peroxide as an initiator to the solution, and then adding maleic anhydride, wherein the molar ratio of polyetheretherketone (PEEK), maleic anhydride and dibenzoyl peroxide is 1:0.04:0.004, slowly heating to 180° C., and maintaining this temperature for 2 hours to initiate a free radical grafting reaction;

[0058] (3) After the reaction is completed, the three-necked flask is taken out from the oil bath and cooled naturally to room temperature. Ethyl acetate in an amount of 4 times the mass of polyetheretherketone is added to the reaction mixture, and the mixture is stirred for 30 minutes to dissolve unreacted maleic anhydride and dibenzoyl peroxide. The reaction mixture is filtered using filter paper, and the precipitate is poured into a large amount of deionized water and stirred for 30 minutes for further washing. After washing, the precipitate is separated and then dried in an oven at 60° C. for 24 hours to obtain the modified polyetheretherketone.

[0059] Example 2

[0060] This embodiment provides a method for preparing modified black phosphorus nanosheets, comprising the following steps:

[0061] (a) selecting a black phosphorus single crystal with a purity greater than 99.99% as a starting material, using a precision diamond tool to cut the black phosphorus single crystal into a thin slice with a thickness of about 50 μm, keeping the environment dry and dust-free during the cutting process to avoid impurity contamination, preparing a 5wt% ammonium persulfate aqueous solution, and adjusting the pH value to 3.0 with dilute hydrochloric acid, completely immersing the cut black phosphorus slice in the ammonium persulfate aqueous solution, and standing at room temperature for 2 hours. After standing, repeatedly rinsing the black phosphorus slice with deionized water until the pH of the washing solution is neutral, and then drying in a 60°C vacuum oven for 12 hours to remove residual moisture;

[0062] (b) adding the dried black phosphorus flakes to N-methylpyrrolidone solvent to make the mass fraction of black phosphorus reach 1.5 mg / mL, placing the mixture in an ice bath and ultrasonically treating it for 30 minutes, the ultrasonic power was set to 200 W, the frequency was 40 kHz, and the ultrasonic treatment was paused every 10 minutes. The sample was taken out and gently shaken to promote a more uniform peeling effect, and then the ultrasonic treatment was continued to obtain a black phosphorus nanosheet suspension;

[0063] (c) preparing an isopropanol solution containing 3-aminopropyltriethoxysilane with a mass concentration of 2%, adding the black phosphorus nanosheet suspension obtained in step (b) to the isopropanol solution of 3-aminopropyltriethoxysilane, heating to 40° C., stirring and reacting for 6 hours, and after the reaction is completed, centrifuging the reactants, washing the solids alternately with deionized water and ethanol three times, and drying the solids in a vacuum drying oven at 80° C. for 24 hours to obtain the modified black phosphorus nanosheets.

[0064] Example 3

[0065] This embodiment provides a method for preparing functionalized graphene quantum dots, comprising the following steps:

[0066] (i) adding graphite powder and a 98% sulfuric acid aqueous solution to a reaction bottle under ice bath conditions, adding potassium permanganate while stirring, maintaining the temperature at 2°C, and stirring for 2 hours to form graphite oxide, adding a 30wt% hydrogen peroxide aqueous solution to the reaction system to terminate the reaction, and washing the graphite oxide with deionized water for multiple times until the pH value of the solution is neutral; wherein the mass volume ratio of graphite powder to sulfuric acid aqueous solution is 1g:25mL, the mass ratio of graphite powder to potassium permanganate is 1:0.5, and the volume of hydrogen peroxide aqueous solution is twice that of sulfuric acid aqueous solution;

[0067] (ii) dispersing the graphene oxide obtained in step (i) in 5 times the mass of deionized water, and ultrasonically treating for 4 hours to obtain a graphene oxide dispersion;

[0068] (iii) mixing the graphene oxide dispersion with hydroiodic acid, heating to 80° C. in a microwave, maintaining for 30 minutes to achieve reduction, cooling to room temperature, adding L-ascorbic acid for further reduction, and stirring at room temperature for 2 hours to obtain a graphene quantum dot dispersion; wherein the mass of the hydroiodic acid is 10 times that of the graphite powder, and the mass of the L-ascorbic acid is 0.5 times that of the graphite powder;

[0069] (iv) adding 4-aminobenzaldehyde to the graphene quantum dot dispersion, wherein the mass of 4-aminobenzaldehyde is 0.1 times of the graphite powder, and stirring at room temperature for 24 hours to achieve functionalization. After stirring, centrifuging and washing the solid matter to obtain the functionalized graphene quantum dots.

[0070] Example 4

[0071] This embodiment provides a black phosphorus polyetheretherketone modified antistatic composite material, which includes the following raw materials by mass: 100 parts of modified polyetheretherketone, 6 parts of modified black phosphorus nanosheets, 2 parts of functionalized graphene quantum dots, 1 part of interface modifier, 0.8 parts of antioxidant, and 2 parts of processing aid;

[0072] The modified polyetheretherketone was prepared according to the method of Example 1.

[0073] The modified black phosphorus nanosheets were prepared according to the method of Example 2.

[0074] The functionalized graphene quantum dots were prepared according to the method of Example 3.

[0075] The interface modifier is a mixture of γ-aminopropyltriethoxysilane, titanium isooctanoate and perfluoropolyether siloxane, with a mass ratio of 4.5:2.5:1.

[0076] The antioxidant is a mixture of antioxidant 168 and antioxidant 1076, with a mass ratio of 1:0.4.

[0077] The processing aid is zinc stearate.

[0078] The preparation method of the black phosphorus polyetheretherketone modified antistatic composite material comprises the following steps:

[0079] (1) adding modified black phosphorus nanosheets, functionalized graphene quantum dots, an interface modifier, an antioxidant and a processing aid into a high shear mixer, setting the speed to 3000 rpm and the mixing time to 15 minutes to obtain a relatively uniform premix;

[0080] (2) adding the premix into a twin-screw extruder, and adding the modified polyetheretherketone at the same time, extruding and granulating the materials after shear mixing, to obtain the black phosphorus polyetheretherketone modified antistatic composite material.

[0081] Example 5

[0082] This embodiment provides a black phosphorus polyetheretherketone modified antistatic composite material, which is different from Example 4 in that it includes the following raw materials, measured by mass: 100 parts of modified polyetheretherketone, 4 parts of modified black phosphorus nanosheets, 1 part of functionalized graphene quantum dots, 2 parts of interface modifier, 0.8 parts of antioxidant, and 3 parts of processing aid; the rest is the same as Example 4.

[0083] Comparative Example 1

[0084] This comparative example provides a black phosphorus polyetheretherketone modified antistatic composite material, which is different from Example 4 in that it includes the following raw materials, measured by mass: 100 parts of modified polyetheretherketone, 10 parts of modified black phosphorus nanosheets, 0.1 parts of functionalized graphene quantum dots, 1 part of interface modifier, 0.8 parts of antioxidant, and 2 parts of processing aid; the rest is the same as Example 4.

[0085] Comparative Example 2

[0086] This comparative example provides a black phosphorus polyetheretherketone modified antistatic composite material, which is different from Example 4 in that the modified polyetheretherketone is replaced by unmodified polyetheretherketone.

[0087] Comparative Example 3

[0088] This comparative example provides a black phosphorus polyetheretherketone modified antistatic composite material, which is different from Example 4 in that maleic anhydride is replaced by methacrylic acid in the preparation of the modified polyetheretherketone.

[0089] Comparative Example 4

[0090] This comparative example provides a black phosphorus polyetheretherketone modified antistatic composite material, which is different from Example 4 in that the modified black phosphorus nanosheets are replaced with black phosphorus powder.

[0091] Comparative Example 5

[0092] This comparative example provides a black phosphorus polyetheretherketone modified antistatic composite material, which is different from Example 4 in that the functionalized graphene quantum dots are replaced by carbon nanotubes.

[0093] Comparative Example 6

[0094] This comparative example provides a black phosphorus polyetheretherketone modified antistatic composite material, which is different from Example 4 in that the interface modifier is a mixture of γ-aminopropyltriethoxysilane, vinyltrimethoxysilane, and methacryloxypropyltrimethoxysilane in a mass ratio of 4.5:2.5:1.

[0095] Performance Testing

[0096] The composite materials prepared in Examples 4-5 and Comparative Examples 1-6 were subjected to performance tests. The tensile strength and elongation at break were tested according to standard ASTM D638, and the volume resistivity was tested according to ASTM D257. The test results are shown in Table 1.

[0097] Table 1 Performance test results

[0098]

[0099]

[0100] It can be seen from the above performance test results that the composite materials prepared in Examples 4-5 have excellent mechanical properties and antistatic properties. Comparative Example 1 adjusts the formula components, especially the content of modified black phosphorus nanosheets is increased, and the functionalized graphene quantum dots are reduced. Excessive modified black phosphorus nanosheets may cause filler agglomeration, affect the uniformity of the internal structure of the material, form stress concentration points, and easily cause crack propagation when subjected to force, thereby reducing tensile strength and elongation at break. Comparative Example 2 uses unmodified PEEK. The interface compatibility between unmodified PEEK and the filler is poor, and effective chemical bonding cannot be formed, resulting in a significant decrease in the mechanical properties of the composite material and an increase in interface defects, making the material more prone to delamination or peeling under stress conditions; unmodified PEEK lacks polar functional groups and is difficult to construct a continuous conductive network, so the antistatic effect is not good. In comparative example 3, methacrylic acid is used instead of maleic anhydride in the modified PEEK. Although methacrylic acid can introduce certain polar functional groups, its reactivity and grafting efficiency with PEEK are lower than those of maleic anhydride, resulting in insufficient interfacial bonding force, which in turn affects the overall mechanical properties of the composite material. In comparative example 4, black phosphorus powder is used instead of modified black phosphorus nanosheets. The black phosphorus powder particles are large and not easy to be evenly dispersed in the composite matrix. It is easy to form agglomerates, causing local stress concentration and reducing the overall mechanical strength of the material. In addition, the rough surface and large particle size of the black phosphorus powder are not conducive to the construction of an efficient conductive network, resulting in an unsatisfactory antistatic effect. In comparative example 5, carbon nanotubes are used instead of functionalized graphene quantum dots. Although carbon nanotubes can also provide a certain conductivity, their compatibility and dispersibility with the PEEK matrix are poor, making it difficult to form an equally efficient conductive network, thereby affecting the antistatic effect. In Comparative Example 6, the interface modifier is changed to a combination of different types of silane coupling agents, which reduces the interface compatibility and adhesion between the inorganic filler and the PEEK matrix, causing the composite material to be more easily delaminated or peeled under stress conditions, thereby reducing the overall mechanical strength.

[0101] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A black phosphorus polyetheretherketone modified antistatic composite material, comprising the following raw materials by mass: 100 parts of modified polyetheretherketone, 3-8 parts of modified black phosphorus nanosheets, 0.5-3 parts of functionalized graphene quantum dots, 0.5-2 parts of interface modifier, 0.5-1 parts of antioxidant, and 1-3 parts of processing aid.

2. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 1, characterized in that: The modified polyetheretherketone is polyetheretherketone modified by grafting with maleic anhydride.

3. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 2, characterized in that: The preparation method of the modified polyetheretherketone comprises the following steps: (1) mixing polyetheretherketone and toluene, heating to 70-90° C., stirring to completely dissolve the polyetheretherketone, and obtaining a mixture; (2) adding dibenzoyl peroxide and maleic anhydride to the mixture of step (1), heating to 170-190° C., and stirring for reaction for 1-3 hours; (3) After the reaction is completed, the reactant is cooled to room temperature, ethyl acetate is added, filtered, and the precipitate is washed with deionized water and dried to obtain the modified polyetheretherketone.

4. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 3, characterized in that: The mass volume ratio of the polyetheretherketone to toluene in step (1) is 1 g:(2-4) mL; the molar ratio of the polyetheretherketone, maleic anhydride and dibenzoyl peroxide is 1:(0.03-0.06):(0.003-0.006).

5. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 1, characterized in that: The preparation method of the modified black phosphorus nanosheets comprises the following steps: (a) cutting a black phosphorus single crystal into thin slices with a thickness of 40-60 μm, immersing the black phosphorus thin slices in an aqueous solution of ammonium persulfate with a concentration of (3-6) wt%, and leaving the solution at room temperature for 1-3 hours, then taking out the black phosphorus thin slices, washing them with deionized water, and drying them; (b) adding the dried black phosphorus flakes to N-methylpyrrolidone solvent to make the mass fraction of black phosphorus reach 1-2 mg / mL, and placing the mixture in an ice bath for ultrasonic treatment for 20-40 minutes to obtain a black phosphorus nanosheet suspension; (c) preparing an isopropanol solution containing 3-aminopropyltriethoxysilane, adding the black phosphorus nanosheet suspension obtained in step (b) to the isopropanol solution of 3-aminopropyltriethoxysilane, heating to 30-50° C., stirring for reaction for 5-8 hours, centrifuging the reactant, washing the solid alternately with deionized water and ethanol, and drying to obtain the modified black phosphorus nanosheet.

6. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 5, characterized in that: The pH value of the ammonium persulfate aqueous solution is adjusted to 2-4; the mass concentration of the isopropanol solution of 3-aminopropyltriethoxysilane is 1.5-2.5%.

7. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 1, characterized in that: The method for preparing functionalized graphene quantum dots comprises the following steps: (i) mixing graphite powder and sulfuric acid in an ice bath, adding potassium permanganate while stirring, maintaining the temperature at 0-5° C., and continuously stirring for 1-3 hours to form graphite oxide. After the reaction is completed, hydrogen peroxide is added to terminate the reaction, and the graphite oxide is washed with deionized water until the pH value of the solution is neutral; (ii) dispersing the graphite oxide obtained in step (i) in water and subjecting it to ultrasonic treatment for 2-5 hours to obtain a graphene oxide dispersion; (iii) mixing the graphene oxide dispersion with hydroiodic acid, heating the mixture to 70-90° C. by microwave, maintaining the mixture for 20-40 minutes, cooling the mixture to room temperature, adding L-ascorbic acid, and stirring the mixture for 1-3 hours to obtain a graphene quantum dot dispersion; (iv) adding 4-aminobenzaldehyde to the graphene quantum dot dispersion, stirring for 20-30 hours, centrifuging and washing the solid matter to obtain the functionalized graphene quantum dots.

8. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 7, characterized in that: The sulfuric acid in step (i) is a sulfuric acid aqueous solution with a mass concentration of 98%, the mass volume ratio of graphite powder to sulfuric acid is 1g: (20-30)mL, and the mass ratio of graphite powder to potassium permanganate is 1: 0.3-0.6; the mass of hydroiodic acid in step (iii) is 8-15 times that of graphite powder, and the mass of L-ascorbic acid is 0.3-0.8 times that of graphite powder; the mass of 4-aminobenzaldehyde in step (iv) is 0.05-0.2 times that of graphite powder.

9. The black phosphorus polyetheretherketone modified antistatic composite material according to claim 1, characterized in that: The interface modifier is a mixture of γ-aminopropyltriethoxysilane, titanium isooctanoate and perfluoropolyether siloxane, with a mass ratio of (4-5): (2-3): 1; the antioxidant is a mixture of antioxidant 168 and antioxidant 1076, with a mass ratio of 1:0.3-0.6; and the processing aid is zinc stearate or calcium stearate.

10. Application of the black phosphorus polyetheretherketone modified antistatic composite material according to any one of claims 1 to 9 in automobile body parts, engine accessories, power battery housings, charging guns and charging piles.

Citation Information

Patent Citations

  • Flame-retardant antistatic glass fiber reinforced nylon 6 composite material and preparation method thereof

    CN112852149A

  • PET (Polyethylene Terephthalate)-based conductive master batch, film and fiber as well as preparation method and application thereof

    CN117165041A

Cited By

  • Photoinduced deformation TPU (thermoplastic polyurethane) material as well as preparation method and application thereof

    CN121758960A